2013
DOI: 10.1021/ie4004927
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward Biomass and Coal-Derived Syngas Warm Cleanup: Proof-of-Concept Process Demonstration of Multicontaminant Removal for Biomass Application

Abstract: Systems comprising multiple sorbent and catalytic beds have been developed for the warm cleanup of coal- and biomass-derived syngas. Tailored specifically for biomass application, the process described here consists of six primary unit operations: (1) a Na2CO3 bed for HCl removal, (2) two regenerable ZnO beds in parallel for bulk H2S removal, (3) a ZnO bed for H2S polishing, (4) a NiCu/SBA-16 sorbent for trace metal (e.g., AsH3) removal, (5) a steam reforming catalyst bed for tars and light hydrocarbon reforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 22 publications
(54 reference statements)
2
27
2
Order By: Relevance
“…For the end-user, tars probably pose the greatest problem from biomass gasification (Torres et al 2007). From a syngas catalytic upgrading perspective, tars can plug catalytic beds or poison the catalyst by physical deactivation or by adsorbing on active sites, where they are known to form carbon deposits and graphitic sheets, i.e., coking (Yung et al 2009;Howard et al 2013). In addition, particulate matter commonly causes corrosion and erosion on downstream process equipment such as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For the end-user, tars probably pose the greatest problem from biomass gasification (Torres et al 2007). From a syngas catalytic upgrading perspective, tars can plug catalytic beds or poison the catalyst by physical deactivation or by adsorbing on active sites, where they are known to form carbon deposits and graphitic sheets, i.e., coking (Yung et al 2009;Howard et al 2013). In addition, particulate matter commonly causes corrosion and erosion on downstream process equipment such as e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although numerous materials have been reported as adsorbents for the effective removal of AsH 3 , high operating temperatures are typically required. [12][13][14][15][16][17][18] For instance, Poulston et al have reported that Pd can be used to modify Al 2 O 3 for the adsorption of AsH 3 from simulated ue gas at temperatures between 204 C and 288 C. 19 Jiang et al found that activated carbon modied with sulfonated cobalt phthalocyanine (CoPcS) and Cu(NO 3 ) 2 was able to adsorb AsH 3 efficiently, and the AsH 3 adsorption capacity was 35.7 mg g À1 adsorbent at 60 C and a 4% oxygen content. 20 However, some shortcomings with the present activated carbons have been identied including their thermal instability.…”
Section: 11mentioning
confidence: 99%
“…The product gas from a biomass gasifier is mainly composed of H 2 , CO, CO 2 , CH 4 , H 2 O, and small quantities of higher hydrocarbon gases such as ethane, organic compounds broadly classified as tars, and inorganic impurities, such as H 2 S, HCl, NH 3 , and alkali metals [2]. Many of these inorganic constituents must be removed to part per billion levels because they strongly interact with downstream watergas-shift and/or synthesis catalysts [3]. Tars are notorious for condensing and subsequently polymerizing on downstream equipment such as compressor and gas turbine surfaces [4].…”
Section: Introductionmentioning
confidence: 99%
“…H 2 S) and catalyst coking are generally the two main reasons for the deterioration of the catalyst performance during steam reforming of biomassderived syngas. In a previous report we demonstrated proof-of-concept for a warm syngas cleanup process that is efficient for removing the inorganic constituents (to ppb level) from the biomass-derived syngas prior to the steam reforming unit [3]. Upon sulfur removal catalyst deactivation due to coking can still be problematic.…”
Section: Introductionmentioning
confidence: 99%